MARRIAGE IN THE IRISH ARISTOCRACY: REPRESENTATION OF WOMEN INFERIORITY - Dewi Pratiwi, - (2011)
The paper entitled " Marriage in the Irish Aristocracy: Representation of Women Inferiority (A Feminist Analysis on the Novel Rebel Daughters by Janet Todd)" aims to identify the representation of women inferiority in Irish Aristocracy and the affect of Aristocracy toward the marriage of main female characters in the novel.The research is qualitative research with textual analysis approach. It employs feminist literary criticism as proposed by K. K. Ruthven to analyze the data which are in the form of words, utterances and expressions taken as textual evidences from the novel Janet Todd's Rebel Daughters. The result of analysis shows that women inferiority in Irish Aristocracy represent in three different ways; women have less opportunity and choice, women are object to please men, women have to be submissive to men's rule and forbidden to give any opinion. Moreover, Aristocracy affects two aspects of the marriage of the main female characters; in matchmaking process and the negotiation of bride price and dowry. It depicts that women in Irish Aristocracy are oppressed by men in every social relationship.